Sifat Fisika dan Mekanika Kayu Acacia aulacocarpa dari KHDTK Wanagama - Nur Indah Lumban Gaol; Fanny Hidayati; Widyanto Dwi Nugroho; Harry Praptoyo; Oka Karyanto; Sri Nugroho Marsoem (Jurnal Ilmu Pertanian Indonesia, 2023)
This study aims to determinethe physical properties and mechanical properties at axial (base, middle, and top) and radial (near the pith, middle, and near the bark) positions, as well as the relationship between the specific gravity and mechanical properties of Acacia aulacocarpa wood. Three 27-year-old trees planted at KHDTK Wanagama wereused. Wood physical and mechanical propertieswere tested per British Standard 373:1957. The statistical analysis used was a two-way ANOVA and a follow-up test of Tukey HSD. The results showed that the average moisture content was 98.95%; the green and air-dry sepesific gravity were 0.58 and 0.61. Radial, tangential, and longitudinal shrinkage from green to oven-dry conditions (total shrinkage) were 2.02%, 5.09%, and 0.33%. The tangential/radial (T/R) ratio was 2.80%. The static bending strength of stress at proportion limit, MoE, and MoR were 498.13 kg/cm2, 116.16x1000 kg/cm2, and 1043.68 kg/cm2, respectively. The compressive strength parallel to the grain and perpendicular to the grain were 596.05 kg/cm2 and 227.25 kg/cm2, respectively. The results of the variance analysis showed that the radial position factor has a significant effect on green moisture content, green and air-dry specificgravity, total radial shrinkage, T/R ratio, static bending strength at stress of proportion limit, MoE, MoR, compressive strength parallel to the grain, and compressive strength perpendicular to the grain. However, the axial position factor did not show any significant differences in the physical and mechanical properties of the wood. Furthermore, air-dry specific gravity has a significant moderate to high positive correlation with all mechanical properties. Keywords: Acacia aulacocarpa, physical properties, mechanical properties, axial position, radial position